UAV aeromagnetic survey of the Acraman impact structure: insights into the central magnetic anomaly - Takáč, Marian; Kletetschka, Gunther; Petrucha, Vojtech (Frontiers in Earth Science, 2025)
The Acraman Crater in South Australia, a deeply eroded Precambrian impact structure, exhibits a prominent central magnetic anomaly linked to its complex impact history. Previous airborne magnetic surveys captured the broad anomaly but lacked the spatial resolution needed to resolve fine-scale, near-surface features critical for subsurface exploration. To address this, we conducted a high-resolution UAV-based magnetic survey over the crater’s central anomaly, employing a dense 25 m profile spacing and 22.5 m survey altitude. This approach revealed discrete, low-amplitude magnetic features and sharp gradient boundaries, identifying previously undetected localized sources. Data processing included Reduction to the Pole (RTP), Analytic Signal (AS), Vertical Derivative (VD), and Tilt Derivative (TDR) methods to enhance spatial interpretation, while depth estimation using Euler Deconvolution and Radially Averaged Power Spectrum (RAPS) provided source depth constraints. The results indicate a structurally complex magnetic source, extending beyond previously assumed boundaries and containing multiple magnetized bodies. These findings provide critical geophysical insights for future drilling, offering refined targets for sampling impact-modified lithologies that could yield valuable age constraints and insights into the impact process, supporting more accurate subsurface models and guiding future geological investigations.